The Evolution of Hours Worked and the Gender Wage Gap: Theory and Evidence from Four Countries - Daniele Checchi; Daniel Kreisman; Cecilia García-Pe\~nalosa (Institute of Labor Economics (IZA), 2025)
We consider the contribution of the intensive margin of labor supply (hours worked above zero) to the gender wage gap across four economies (Germany, France, US, UK) over a long time-horizon. We first build a model in which firms offer two wage contracts – one that pays a fixed wage but allows workers to choose their preferred number of hours up to "full time", and a second in which wages are relative to imperfectly observable productivity but hours can be limitless. The former includes part- and full-time work, while the latter represents a class of workers who often must supply very long hours but who can then earn potentially unlimited remuneration. We then apply a Oaxaca decomposition for part-, full-, and over-time workers to observe the relative contribution of sorting and remuneration across these hours "regimes" over time and across countries. Through this, we show that while female employment in over-time work increased and the gender wage decreased, this was not driven by increasing selection but rather by a decrease in the unexplained portion of the wage gap over time. We conclude by considering the contribution of unions and labor market flexibility to these cross-country differences.
Keywords: J01; J16; J31; 330; labor supply; gender wage gap; over-time work; Oaxaca decomposition